Pengaruh Model Pembelajaran Problem Posing terhadap Hasil Belajar Peserta Didik Kelas VIII - Iis Nuriyah Prihartini; Nurhayani H. Muhiddin; Hasanuddin Hasanuddin (Universitas Negeri Makassar, 2025)
This study aims to determine (1) the cathegory of learning outcomes of VIII grade students at MTsN 1 Mamuju who is teach using the problem posing learning model (2) the category of learning outcomes of VIII grade students at MTsN 1 Mamuju who is teach using conventional learning models. (3) whether there are an effects of the problem posing learning model on the learning outcomes of class VIII students at MTsN 1 Mamuju on the material of the human respiratory system. The type of research used in this study is a True Experimental Design research (True Experimental Design) and the design of this research plan is Posttest Only Control Design. The population of this study were all students in grade VIII at MTsN 1 Mamuju. The sample was selected using Simple Random Sampling technique and obtained class VIII.3 20 students and VIII.4 22 students. The research instrument was a learning outcome test question. Data were analyzed with descriptive and inferential statistics. The results of the study concluded: (1) The level of science learning outcomes of students in class VIII MTsN 1 Mamuju who is teach using the problem posing learning model is in the medium category with an average score of 11.18. (2) The level of science learning outcomes of students in class VIII MTsN 1 Mamuju who is teach using conventional learning is in the medium category with an average score of 9. (3) There are an effect of the problem posing learning model on the science learning outcomes of students in class VIII MTsN 1 Mamuju on the material of the human respiratory system.